Alterations of amygdala-prefrontal connectivity with real-time fMRI neurofeedback in BPD patients - Paret, Christian; Bohus, Martin; Ende, Gabriele; Schmahl, Christian (Social cognitive and affective neuroscience, 2016)
With the use of real-time functional magnetic resonance imaging neurofeedback (NF), amygdala activitiy can be visualized in real time. In this study, continuous amygdala NF was provided to patients with borderline personality disorder (BPD) with the instruction to down-regulate. During four sessions of NF training, patients viewed aversive pictures and received feedback from a thermometer display, which showed the amygdala blood oxygenation level-dependent signal. Conditions of regulation and viewing without regulation were presented. Each session started with a resting-state scan and was followed by a transfer run without NF. Amygdala regulation, task-related and resting-state functional brain connectivity were analyzed. Self-ratings of dissociation and difficulty in emotion regulation were collected. BPD patients down-regulated right amygdala activation but there were no improvements over time. Task-related amygdala-ventromedial prefrontal cortex connectivity was altered across the four sessions, with an increased connectivity when regulating vs viewing pictures. Resting-state amygdala-lateral prefrontal cortex connectivity was altered and dissociation, as well as scores for ‘lack of emotional awareness’, decreased with training. Results demonstrated that amygdala NF may improve healthy brain connectivity, as well as emotion regulation. A randomized-controlled trial is needed to investigate whether amygdala NF is instrumental for improving neural regulation and emotion regulation in BPD patients.